1986
DOI: 10.1016/0022-3115(86)90126-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue behavior of irradiated helium-containing ferritic steels for fusion reactor applications

Abstract: The martensitic alloys 12Cr-lMoVW and 9Cr-lMoVNb have been irradiated in the High Flux Isotope Reactor (HFIR) and subsequently tested in fatigue. In order to achieve helium levels characteristic of fusion reactors, the 12Cr-lMoVW was doped with 1 and 2% Ni, resulting in helium levels of 210 and 410 at. ppm at damage levels of 25 dpa. The 9Cr-lMoVNb was irradiated to a damage level of 3 dpa and contained <5 at. ppm He. Irradiations were carried out at 55°C and testing at 22°C. No significant changes were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…It was reported that the Fe-9Cr-1MoVNb steel irradiated at 323 K did not show a reduction of N f even at De t of 0.3% [14]. In this steel, it is expected that the channel fracture dose not occur and therefore the effect of dislocation channeling on plastic deformation behavior is not significant.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was reported that the Fe-9Cr-1MoVNb steel irradiated at 323 K did not show a reduction of N f even at De t of 0.3% [14]. In this steel, it is expected that the channel fracture dose not occur and therefore the effect of dislocation channeling on plastic deformation behavior is not significant.…”
Section: Discussionmentioning
confidence: 94%
“…It was seen in previous fatigue test results of ion-irradiated RAF/Ms specimens [4,6] that larger reduction of N f occurred in specimens tested at 553-693 K with De t of about 0.6%. These specimens were irradiated at temperature of 523-693 K. The martensitic steel Fe-9Cr-1MoVNb irradiated at 328 K to 3 dpa did not exhibit the reduction of N f at De t of 0.3-0.5% [14]. It is considered that the reduction of N f at De t of about 0.5% is related to the irradiation temperature.…”
Section: Discussionmentioning
confidence: 99%
“…al. [19] concluded that little or no effect of irradiation was on the fatigue life. Furthermore, Bertsch et al [20] showed that the fatigue life of irradiated specimen was reduced at high strain range (e t = 0.9 Â 10 4 ) test and was slightly increased at low strain range (e t < 0.5 Â 10 4 ) test.…”
Section: Bend-fatigue Propertiesmentioning
confidence: 97%
“…There are not many data on fatigue life of irradiated FM steels [14][15][16][17][18][19][20], and they are obtained by axial strain-controlled fatigue tests. There are no data on bend fatigue life of irradiated specimens.…”
Section: Bend-fatigue Propertiesmentioning
confidence: 99%
“…Gelles [48] recently reported results of irradiations of Cr-Mo steels conducted in a fast neutron spectrum (FFTF) showing that adequate toughness is maintained for damage levels up to 100 dpa. Grossbeck et al [49] investigated the fatigue behaviour of irradiated ferritic steels and found indications that in 12Cr-lMo-V-W, helium at levels of 210 and 410 appm provided cyclic strengthening over the unirradiated condition. These results suggest that the higher helium levels produced in these alloys in the mixed spectrum reactor irradiations, which are more characteristic of fusion damage, have an effect on the deformation and fracture behaviour.…”
Section: Martensitic Steelsmentioning
confidence: 99%